2021
DOI: 10.3389/fpsyg.2021.708751
|View full text |Cite
|
Sign up to set email alerts
|

Stakes of Knowing the Truth: A Motivational Perspective on the Popularity of a Controversial Scientific Theory

Abstract: The aim of this article is to provide a different perspective on people's beliefs regarding controversial scientific information. We emphasize that, although people generally aim at getting a fair representation of reality, accuracy about scientific issues only matters to the extent that individuals perceive it as useful to achieve their own goals. This has important consequences in terms of how anti-science attitudes as well as epistemically questionable beliefs must be interpreted, which has consequences for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
6
0
3
Order By: Relevance
“…In the survey by Brennen et al [13] , top-down misinformation about COVID-19 was identified from politicians, celebrities, and other prominent public personalities, accounting for 20% of the claims and 69% of total social media engagement. In France, a virologist living in Marseille, France was a great disseminator of false information on hydroxychloroquine (HCQ) [39] .…”
Section: Cognitive Factorsmentioning
confidence: 99%
“…In the survey by Brennen et al [13] , top-down misinformation about COVID-19 was identified from politicians, celebrities, and other prominent public personalities, accounting for 20% of the claims and 69% of total social media engagement. In France, a virologist living in Marseille, France was a great disseminator of false information on hydroxychloroquine (HCQ) [39] .…”
Section: Cognitive Factorsmentioning
confidence: 99%
“…This disposition, first coined by John Flavell (1979), is all the more important in the evaluation of scientific information as such information is often not intuitive, and can have high social stakes. The tendency to take a metacognitive stance on our own trusting attitudes is encouraged by the importance of having an accurate representation of reality on a given issue (Morisseau, Branch and Origgi 2021).…”
Section: Conclusion: Good Use Of Reputational Cuesmentioning
confidence: 99%
“…Over subsequent months, several randomized clinical trials reported that hydroxychloroquine, alone or in combination with azithromycin, was ineffective at preventing SARS-CoV-2 transmission, providing more rapid resolution of clinical symptoms or reducing hospital admissions and mortality in COVID-19 patients, and was associated with no improved mortality compared to placebo ( 2 , 3 , 4 , 5 ). Nevertheless, despite these consistent data, and the publication of the living World Health Organization (WHO) guidelines recommending against the use of hydroxychloroquine in COVID-19 ( 6 ), the “effectiveness” of this drug is still asserted by some, who are using social networks and the media to spread their beliefs ( 7 , 8 ). This (mis)information created doubt, angry debate, and even threats to hydroxychloroquine detractors.…”
mentioning
confidence: 99%